Pengaruh Total Quality Management (TQM), Servant Leadership, dan Komitmen Organisasi Terhadap Kinerja Organisasi Pada Rumah Sakit di Kota Serang, Kota Cilegon, dan Kabupaten Serang - Nisauzakiyah, Dina; Bastian, Elvin (Universitas Pahlawan Tuanku Tambusai, 2024)
The prospect of improving the quality of health services in a sustainable manner is a policy supported by all work units through an efficient and effective Total Quality Management (TQM) implementation program. Service companies that are committed to providing the best service and continuously improving processes will progressively improve company performance, this is in accordance with the role of servant leadership who can build a culture in implementing this, and the company also needs a strong organizational commitment so that employees will work harder, be able to collaborate, and strive to achieve organizational goals. This study intends to partially examine the influence of Total Quality Management (TQM), Servant Leadership, and Organizational Commitment on Organizational Performance. The sample in the study amounted to 88 respondents, the purposive sampling technique was used. Primary data was obtained from the results of the questionnaire distribution and then analyzed using the help of SPSS version 25. The findings of the study show that Total Quality Management (TQM), Servant Leadership, and Organizational Commitment have a significant positive influence on Organizational Performance partially.